Analisis Yuridis atas Amandemen Undang-Undang Angkatan Bersenjata Nasional Indonesia dan Keseimbangan Sipil-Militer - Azzahra, Nurrefa; Siswanti, Eviana; Fartini, Ade; Nabilla, Allivia (Institut Agama Islam (IAIN) Kendari, 2026)
This study examines the 2025 amendment to the Indonesian National Armed Forces Law (TNI Law), which has revived debate over the boundary between military and civilian roles and its consequences for the balance of power in a constitutional democracy. The central problem lies in the amendment’s tendency to expand military involvement beyond its defense mandate through broader access for active-duty officers to civilian posts, the expansion of Military Operations Other Than War (OMSP), and insufficient legal safeguards to restrain military intervention in government affairs. The study aims to analyze the amendment as a juridical issue concerning the distribution of authority, accountability patterns, civilian control, and checks and balances between military and civilian institutions. This research employs a normative legal method and a qualitative approach, based on secondary data collected through document study and library research on legislation, legal documents, and relevant scholarly works. The findings show three main points. First, the revised norms create ambiguity and regulatory gaps that enable the expansion of civilian positions for active-duty officers. Second, the amendment may generate overlapping authority, accountability conflicts, and weakened civilian control within the bureaucracy. Third, expanded military involvement in civilian offices threatens TNI professionalism and signals post-reform remilitarization. These findings indicate that the amendment cannot be understood as an ordinary administrative adjustment. The study therefore implies the need for constitutional correction, clearer legal limits on military roles, and stronger civilian oversight to safeguard constitutional democracy.